2003
DOI: 10.1210/jc.2002-021353
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroid Hormone Receptors in Human Thymoma

Abstract: In this study we examined the immunohistochemical localization of sex steroid receptors for estrogen alpha (ER alpha) and ER beta, progesterone-A (PR-A) and PR-B, and androgen (AR) in human thymoma (n = 132) and correlated these findings with various clinicopathological parameters. We used RT-PCR and real-time PCR to further study the expression of these receptors in 20 thymoma cases. Immunoreactivity for all sex steroid receptors was detected in the nuclei of thymoma epithelial cells. The percentage of immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
158
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(162 citation statements)
references
References 30 publications
1
158
1
2
Order By: Relevance
“…This result indicates that the high expression of ERa noted in the earlier mentioned study may be because of a cross-reaction with ERb. To the best of our knowledge, there was only 1 report published to date analyzing ERb expression in thymomas, and the expression rate was extremely low (7%) 38 compared with that observed in the current study. This discrepancy may be because of differences in the patient population, source of antibody, dilution, method of antigen retrieval, and scoring system.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…This result indicates that the high expression of ERa noted in the earlier mentioned study may be because of a cross-reaction with ERb. To the best of our knowledge, there was only 1 report published to date analyzing ERb expression in thymomas, and the expression rate was extremely low (7%) 38 compared with that observed in the current study. This discrepancy may be because of differences in the patient population, source of antibody, dilution, method of antigen retrieval, and scoring system.…”
Section: Discussioncontrasting
confidence: 79%
“…The previous study also demonstrated low expression rates of PgR-A (4%) and AR (15%). 38 These results indicate that PgR-A and AR have low potential as targets for therapy and have little involvement in thymoma and thymic tumorigenesis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A mean expression index was calculated to represent the protein expression of LHR or FSHR in each ovarian tissue section from an individual animal [14], [15] and [16].…”
Section: Ei = %Total Stained Cells X [(1 X %Weak) + (2 X %Medium) + (mentioning
confidence: 99%
“…Briefly, 500 cells of interest (tumour or macrophages) were counted, and an H-score was generated by adding the percentage of strongly stained nuclei multiplied by 3, the percentage of moderately stained nuclei multiplied by 2, and the percentage of weakly stained nuclei multiplied by 1, giving a possible score of range of 0-300 [19].…”
Section: Immunohistochemistrymentioning
confidence: 99%